Analisis Penerapan Akuntansi Lingkungan Pada Pengolahan Limbah Rumah Sakit (Studi Kasus Rumah Sakit Umum Daerah Dr. Pirngadi Kota Medan) - Hizrahtul Darsani; Nurlaila Nurlaila; Rizqa Amelia (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This research aims to determine the application of environmental accounting in waste processing at RSUD Dr. Pirngadi, Medan City. The data analysis method in this research uses descriptive qualitative analysis. The data collection techniques used were observation, interviews and documentation studies. In analyzing environmental accounting in hospital waste processing at RSUD Dr. Pirngadi, Medan City, researchers used descriptive analysis steps, including collecting financial report data at Dr. Pirngadi Medan City in 2022, identified the environmental costs of RSUD Dr. Pirngadi Medan City, analyzing its environmental responsibilities, and drawing conclusions. The results of this research are Dr. Pirngadi Medan City has identified environmental costs according to Hansen and Mowen's theory, but Dr. Pirngadi Medan City has not implemented environmental accounting for environmental costs in managing its waste. This is due to environmental cost reports at RSUD Dr. Pirngadi, Medan City, has not been presented explicitly in the financial report of RSUD Dr. Pirngadi, Medan City.